Mitigation of the effect of secondary salinization by micro soil conditioning - Rivera Garcia, Arzu; Tuba, Géza; Czellér, Krisztina; Kovács, Györgyi; Zsembeli, József (Acta Agraria Debreceniensis, 2020)
This research has the general goal to meet the customization of agriculture in small scale farming. We are developing a technique using micro doses of soil conditioners and organic material applied in the root zone of vegetable crops. We expected to change the physical and chemical properties of the affected soil, which has been irrigated with salty water. Two different soil conditioners were tested. A lysimeter experiment including 8 simple drainage lysimeters was set up in the Research Institute of Karcag IAREF University of Debrecen in 2017. The main goal was to study the effect of different soil conditioners on the soil endangered by secondary salinization induced by irrigation with saline water. In order to compare the difference between the treatments, we collected soil samples, water samples, and determined the yields. Chili pepper (Capsicum annuum) was used as an indicator crop during one specific agricultural season. The technique called micro soil conditioning is rational because several reasons. The roles of the technique are various, for example it can serve as a source of carbon or a container for soil amendments and can minimize evaporation. We found this technique not to interfere with the chemical reaction or the interaction with the plants. However, the micro doses of soil amendments had the role to minimize the risk of soil degradation and do not significantly influence soil respiration. In addition, by improving soil properties, soil conditioning increases the leaching of the excess of salts from the root zone. In fact, this technique can decrease the cost of the inputs and improves the production of vegetables, and at the same time mitigates the effect of secondary salinization.